2019
DOI: 10.2298/tsci170419216k
|View full text |Cite
|
Sign up to set email alerts
|

Boiling heat transfer of nanofluids: A review of recent studies

Abstract: Adding solid particles of nanometer scale to fluids is one of the most important passive methods of enhancing heat transfer performance. However, this gives numerous chances to investigate new frontiers, but also raises remarkable difficulties. Nanofluids act as suspension that can be obtained by dispersing nanometer-sized nanoparticles (1-100nm) in host fluids with the aim of enhancing thermal properties. This paper is a review of recent studies on boiling heat transfer of nanofluids for pool and convective f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The high heat transfer rate that could be removed during this heat transfer mode was a massive motivation for the researchers of the heat transfer area to understand well this physical phenomenon. Boiling and twophase flow encountered in various industrial applications such as boilers tubes, evaporators, air conditioning, cooling of high heat flux dissipation electronic systems, cooling of nuclear reactors, some chemical process [1][2][3][4][5][6]. Pool boiling is a type of boiling that involves boiling of the stationary liquid inside the vessel (boiling chamber), and it is encountered in the aforementioned industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…The high heat transfer rate that could be removed during this heat transfer mode was a massive motivation for the researchers of the heat transfer area to understand well this physical phenomenon. Boiling and twophase flow encountered in various industrial applications such as boilers tubes, evaporators, air conditioning, cooling of high heat flux dissipation electronic systems, cooling of nuclear reactors, some chemical process [1][2][3][4][5][6]. Pool boiling is a type of boiling that involves boiling of the stationary liquid inside the vessel (boiling chamber), and it is encountered in the aforementioned industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…Fiorelli [23] Pool and flow boiling/HTC They concluded regarding boiling of nanofluids that the interaction between the nanoparticles and the heating surface is the main reason to enhance or decrease the heat transfer performance and it is also could increase the critical heat flux. They also reported that the studies associated with flow boiling of nanofluids are rear and need more efforts to understand this mechanism Kamel and Lezsovits [24] Pool and flow boiling/HTC, CHF and other related parameters…”
Section: Recent Review Papers Related To the Boiling Of Nanofluidsmentioning
confidence: 99%
“…Kamel and Lezsovits [24] presented the state-of-the-art overview on the subject of boiling heat transfer by using nanofluid and briefly discussed the latest experimental and theoretical studies related to this topic. Their review focused on the works that have done from 2012 until the beginning of 2017.…”
Section: Recent Review Papers Related To the Boiling Of Nanofluidsmentioning
confidence: 99%
“…Nucleate pool boiling regime, and two-phase flow have a variety of industrial applications such as boiler tubes in power plant, evaporators in refrigeration systems, cooling of macro and microelectronic devices, and cooling of nuclear reactors, etc. [1][2][3]. Removing high heat dissipation with a miniaturization system has always been a key point for designing efficient heat exchange systems.…”
Section: Introductionmentioning
confidence: 99%